Dynamic Tensile Properties of Granite Varied with Depths under a Similar Loading Rate. (22nd November 2018) - Man, Ke; Wang, Ju; Liu, Xiaoli
Abstract : Based on the SHPB device, the dynamic tensile test was carried out on the granite, which is located at the depth 350 m∼580 m at the same borehole in TianHu area Xinjiang Province, the preselected site of the high-level radioactive waste geological disposal in China. Under the loading rate level of 10 5  MPa/s, the dynamic tensile strength is generally between 15 MPa∼35 MPa, which is of significant reference for the site selection. No matter whatever the depth, the dynamic tension strength increases with the loading rate, which shows the loading rate effect of brittle material. Meanwhile, the failure model is also tension pattern, which is the same as the static tension test. Furthermore, as the physical characteristics of the rock have been changed gradually, the rock strength and other mechanical properties will increase or decrease with the depth. From the point of physical mechanism, the density, porosity, and others are different at diverse depths, which lead to the differences of mechanical properties. And the result and the theoretical knowledge could be applied to the blasting and excavation of deep geoengineering and HLW geodisposal.